(untitled) (AYUSHDHARA, 2015)
The medication of normal procedure shall be extra legitimate if the ailment is identified by using it’s possess viewpoint. So the be taught was once aimed to determine the sensitivity and specificity of the Siddha diagnostic methodology. Siddha strongly advocacies every physician to seem into “what type of person is suffering from an ailment is most important than what variety of health problem he has”. This holistic standpoint devises the protocol of each medication in Siddha. This distinctive primary is the delicate force and motive in the back of the existence of this method considering antiquity. Having the above mentioned unique standards in intellect, this paper tried to fully grasp the complexity and core basics of Siddha diagnostics which indeed pave solution to unique therapeutics. The medication of normal system shall be more legitimate if the disorder is diagnosed via its own point of view. So the learn was once aimed to check the sensitivity and specificity of the Siddha diagnostic ways. Eight fold examinations displays particularly pulse studying, tongue, complexion, voice, eyes, physique examination, stool and urine. These instruments provide the framework in phrases of immediate and individualized prognosis and medication to the patient and support to recover from diseases in a timely fashion without leaving any hazardous impact on the physique.